SPAC IPOs - Yochanan Shachmurove; Milos Vulanovic (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2018)
Specified Purpose Acquisition Companies (SPACs) are a special type of public companies currently available to investors in financial markets. As an investment vehicle, modern SPACs are traced back to 18-th century England where blank checks were first mentioned as blind pools during the infamous South Sea Bubble. In the United States, the Security and Exchange Commission classifies SPAC as a blank check company. This chapter reviews the academic and financial literatures about SPACs, describes their institutional characteristics and analyses their market performance since Initial Public Offering (IPO). The sole purpose of SPACs is to use the proceeds to finance future acquisition.
Keywords: G12; G32; G14; G24; 330; Blank checks; Initial public offering (IPO); IPO survival; Mergers and Acquisition (M&A); Specified Purpose Acquisition Companies; SPACs